PEMBENTUKAN KADER RAPID SEBAGAI UPAYA PENCEGAHAN PENYAKIT DEGENERATIF (DIABETES MELLITUS) DI KELURAHAN WONOROMO SURABAYA - -, UMDATUS SOLEHA; -, SITI NURJANAH (JURNAL PENGEMBANGAN KOMUNITAS, 2018)
Degenerative diseases can occur to anyone, either because of age and poor lifestyle. Degenerativediseases suffered by many people include hypertension, coronary heart disease, diabetes mellitus,osteoarthritis, osteoporosis etc. Community service activities undertaken in Wonokromo VillageSurabaya has the aim of increasing the role of the community in preventing the occurrence ofdegenerative diseases through the establishment of "RAPID" Cadre for the community. Through theRAPID Cadre, the community will have adequate knowledge, be able to be positive and have positivebehaviors in health care. Through community service activities formed RAPID Cadre, where this cadrewill actively play a role in the prevention of various degenerative diseases that can be suffered bysociety. The establishment of this cadre begins by debriefing the cadre about the knowledgepreviously pre-tested. Demonstration of the cadres with adequate knowledge, is expected to be ableto become educators or community counselors in improving their health and prevent variousdegenerative diseases. The presence of RAPID Cadres can help to improve prevention and healthpromotion.